PENGEMBANGAN MANAJEMEN PEMBELAJARAN PENDIDIKAN JASMANI OLAH RAGA DAN KESEHATAN SERTA FUNGSI PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR SISWA DI SD NEGERI GRABAG 1 (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study is a qualitative research . The research was conducted in primary schools with the aim Grabag 1 1. To describe the management development of physical education, sport and health are implemented in Elementary School District Grabag Grabag 1 2. To describe the role of sport and physical education and health to the achievement motivation of the teaching and learning in primary schools Grabag 1 District Grabag ? 3. Knowing the obstacles encountered in teaching physical education and sport in primary school health Grabag 1 ? 4. Knowing how to overcome the learning obstacles sports physical education and health in relation to motivation and student achievement in elementary school Grabag 1 ? The problem formulation in this study is : How can learning management of physical education , sport and health are implemented on motivation and learning achievement in primary schools Grabag 1 District Grabag ? 2. What is the role of physical exercise and health education on motivation and achievement of the teaching and learning in primary schools Grabag 1 Subdistrict Grabag1 ? 3. What are the obstacles encountered in teaching physical education and sport in primary school health grabag 1 ? 4. How to overcome learning obstacles sports physical education and health in relation to motivation and student achievement in elementary school Grabag 1 . The results showed that with good management proved that the Elementary School Negeri Grabag 1 may showed that there was a symbiosis mutualism between physical exercise and health education with other subjects . Research can showed that physical education and health sport by some parties only regarded as supplementary lessons that do not require special profesionalesme of teaching was not true . Sports physical education and health is one of the subjects which, if done by a professional teacher who was able to give a good contribution to spur students to excel in other subjects . With the reciprocal function can encourage learners to enhance in the field of academic and nonacademic.